Microstructural evolution during deformation of tin dioxide nanoparticles in a comminution process - Armstrong, Patrick; Knieke, Catharina; Mackovic, Mirza; Frank, Gerhard; Hartmaier, Alexander; Göken, Mathias; Peukert, Wolfgang; Mackovic, Mirza (Acta Materialia, 2009)
Nanoparticles can be produced by wet grinding in stirred media mills if agglomeration is prevented by stabilization of the particles. Since the fracture mechanisms at the lower nanoscale are not yet understood, we studied the evolution of the microstructure within tin dioxide particles. Electrostatic stabilization allows the formation of tin dioxide with a mean particle size of 25 nm as measured by dynamic light scattering. High-resolution transmission electron microscopy (HRTEM) images show particles well below 10 nm and mean crystallite sizes of 9 nm were obtained from X-ray diffraction by applying the Rietveld refinement method. Additionally, TEM and HRTEM analyses were conducted to gain detailed insight into the microstructural effects governing the grinding process. Microscopy revealed surprisingly rich phenomena including the formation of shear bands, twinning and stacking faults that directly affect the grinding behavior. Interestingly the ceramic nanoparticles showed not only fracture patterns expected from brittle fracture but also many traces of plastic deformation. For comparison the uniaxial compression of particles up to 30 nm in diameter was simulated using molecular dynamics. The simulated particles shared microstructural details with the real samples, most importantly the shear bands which lead to significant plastic deformation. The internal microstructure produced during multiple particle stressing events in the mill and also observed in the simulations is directly linked to the fracture mechanism and the experimentally observed grinding limit. © 2009 Acta Materialia In
UnivIS-Import:2015-03-09:Pub.2009.tech.IW.LM.micros
Keywords: Molecular dynamics simulations; Nanomechanics; Nanostructure; Shear bands; Transmission electron microscopy (TEM)